Seasonal variation in helminth parasite infections in Oreochromis niloticus from sewage ponds in Kano State, Nigeria - MaarufAbdu, Habibu; Shah, Mohammad Manjur (Recent Research in Science and Technology, 2025)
This study assessed the seasonal variation in helminth parasite infections in Oreochromis niloticus from sewage ponds in Gwale Local Government Area, Kano State, Nigeria. A total of 385 tilapia fish were examined over a 15-month period from January 2024 to March 2025, spanning both dry and rainy seasons. Standard parasitological techniques were used to recover helminths from the gastrointestinal tract and gills. The overall prevalence of infection was significantly higher during the rainy season (48.2%) than in the dry season (18.7%) (χ²=27.16, p<0.001). Three helminth species were identified: Clinostomum spp., Euclinostomum sp., and Polyonchobothrium polyepteri. Trematodes dominated the infection profile, with a peak in parasite recovery between July and September. These results show the influence of rainfall and seasonal ecological shifts on helminth transmission dynamics and emphasize the need for targeted health and food safety measures during high-risk periods.